Change in Lipofectamine Carrier as a Tool to Fine-Tune Immunostimulation of Nucleic Acid Nanoparticles - Hannah S. Newton; Yasmine Radwan; Jie Xu; Jeffrey D. Clogston; Marina A. Dobrovolskaia; Kirill A. Afonin (Molecules, 2023)
Nucleic acid nanoparticles (NANPs) require a carrier to allow for their intracellular delivery to immune cells. Cytokine production, specifically type I and III interferons, allows for reliable monitoring of the carrier effect on NANP immunostimulation. Recent studies have shown that changes in the delivery platform (e.g., lipid-based carriers vs. dendrimers) can alter NANPs’ immunorecognition and downstream cytokine production in various immune cell populations. Herein, we used flow cytometry and measured cytokine induction to show how compositional variations in commercially available lipofectamine carriers impact the immunostimulatory properties of NANPs with different architectural characteristics.